(3fRhd GdZjK GdPj GfSLe aj TQM dGejI GdYLes - (3eMeO Hf CHj HcQ Hf YeQ Hf CHj HcQ Hf eMeO, GdeNRhej GdbQTj, HOQ GdOjf GdeYQha HGHf GdOeGejfj , J (B827 (3g` s; (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s ((3Ydj GdCMeOi GdejbGJj GdMfaj s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPj dG jJhLg Ydjg GdEYJQGV aEf HYV ScGf GdEScfOQjI, eef jRYe Cfg ef WdHg GdYde s
(3BNQgG (B:s
(3eY Cfj JQcJ CTjGA de CPcQgG Nha GdEWGdI hGdedd adjbJUQ Ydi gPG GdbOQ aajg caGjI, hGdg GSCd MSf GdNGJeI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3JYbH ajg TQM dGejI GdYLe dUdGM GdOjf GdUaOj hGdeSei (B"(3GdZjK GdeSLe aj TQM dGejI GdYLes
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
Keywords: (3GdCOHs